Study of Interactions of an Anticancer Drug Neratinib With Bovine Serum Albumin: Spectroscopic and Molecular Docking Approach - Wani, Tanveer A.; Bakheit, Ahmed H.; Abounassif, M. A.; Zargar, Seema (Frontiers in Chemistry, 2018)
Binding of therapeutic agents to plasma proteins, particularly to serum albumin, provides valuable information in the drug development. This study was designed to evaluate the binding interaction of neratinib with bovine serum albumin (BSA). Neratinib blocks HER2 signaling and is effective in trastuzumab-resistant breast cancer treatment. Spectrofluorometric, UV spectrophotometric, and fourier transform infrared (FT-IR) and molecular docking experiments were performed to study this interaction. The fluorescence of BSA is attributed to the presence of tryptophan (Trp) residues. The fluorescence of BSA in presence of neratinib was studied using the excitation wavelength of 280 nm and the emission was measured at 300-500 nm at three different temperatures. Neratinib quenched the BSA intrinsic fluorescence by static mechanism. A complex formation occurred due to the interaction leading to BSA absorption shift. The fluorescence, UV- absorption, three dimensional fluorescence and FT-IR data showed conformational changes occurred in BSA after interaction with neratinib. The binding constant values decreased as the temperature increased suggesting an instable complex formation at high temperature. Site I (sub-domain IIA) was observed as the principal binding site for neratinib. Hydrogen bonding and Van der Waals forces were suggested to be involved in the BSA-neratinib interaction due to the negative values of entropy and enthalpy changes.